Rancang Bangun Sistem Informasi Monitoring Kinerja THL Di DISBUDPAR Kota Tangerang - Fridayanthie, Eka Wulansari; Sayfulloh, Asep; Putra, Anugrah Eka; Septiani, Lidya; Tanjung, Muhammad Ramadhan (Swabumi, 2025)
Penelitian ini membahas pelaksanaan sistem informasi website e-kinerja THL sebagai sarana pemantauan aktivitas pegawai di Dinas Kebudayaan dan Pariwisata Kota Tangerang. Temuan penelitian mengindikasikan bahwa sistem ini berpengaruh besar terhadap peningkatan efisiensi kerja. Website e-kinerja mempermudah Kasubag dan Sekretaris Dinas dalam mengawasi aktivitas harian THL secara langsung dan terpusat, serta meningkatkan efisiensi pelaporan karena THL bisa mengisi laporan secara online. Di samping itu, sistem ini mengurangi pemakaian dokumen fisik, menyajikan data kinerja yang terstruktur dan terdokumentasi, serta mempercepat evaluasi dan rekapitulasi laporan. Transparansi dan akuntabilitas pegawai menjadi semakin baik, karena semua data aktivitas terdokumentasi secara teratur. Fitur pencarian yang berdasarkan nama, tanggal, dan tipe kegiatan juga mempermudah dalam melacak data. Sistem informasi ini dianggap dapat mendukung pengelolaan kinerja pegawai secara digital, efisien, dan terintegrasi.This study discusses the implementation of the THL e-performance website information system as a means of monitoring employee activities at the Tangerang City Culture and Tourism Office. The findings indicate that this system has a significant impact on improving work efficiency and supervisory effectiveness. The e-performance website makes it easier for the Head of Subdivision and Secretary of the Office to monitor the daily activities of THL directly, in real time, and centrally. Additionally, the system improves reporting efficiency as daily contract workers can submit activity reports online without the need for physical documents. The system also accelerates the evaluation and compilation process, reduces the risk of data loss, and enhances reporting accuracy. Performance data is systematically stored, making it easier to review when necessary. The search feature based on name, date, and activity type greatly assists in the monitoring process. This system supports the principles of transparency and accountability, as all activities are clearly documented and can be accounted for. Overall, the THL e-performance information system is considered capable of supporting the digitalization of employee performance management efficiently, modernly, and integrally, and making a tangible contribution to achieving better governance that is responsive to technological developments.